PERSEPSI GURU SMA NEGERI 1 SEKAMPUNG TERHADAP RENCANA PELAKSANAAN KURIKULUM 2013 - Suhandi Wibowo; Holilulloh Holilulloh; M.Mona Adha (FKIP Unila, 2013)
The purpose of this study is to set out in the opinion of the teachers of SMAN 1 Sekampung 2013 curriculum implementation plan based on the teacher's perception of itself. This research method is descriptive quantitative, population in this study were all teachers of SMAN 1 Sekampung which totaled 36 people. Data collection technique used is the questionnaire which is then performed with the data processing formula percentage.Teachers' perceptions about the components of the curriculum objectives in 2013 are in the category of support (55.6%). teachers' perceptions of the content of the curriculum components in 2013 are in the category of support (47.2%). teachers' perceptions about the component method on the curriculum in 2013 to be in the category of support (58.3%). perceptions about the teacher evaluation component to the curriculum in 2013 to be in the category does not support (50%).Tujuan penelitian ini adalah adalah untuk memaparkan pendapat guru SMAN 1 Sekampung tentang rencana pelaksanaan kurikulum 2013 berdasarkan persepsi guru itu sendiri. Metode penelitian ini adalah deskriptif kuantitatif, populasi dalam penelitian ini adalah seluruh guru SMAN 1 Sekampung yang berjumlah 36 orang. Teknik pengumpulan data yang digunakan adalah dengan angket yang selanjutnya dilakukan pengolahan data dengan rumus prosentase. Persepsi guru tentang komponen tujuan pada kurikulum 2013 berada dalam katagori mendukung (55,6 %). persepsi guru tentang komponen isi pada kurikulum 2013 berada dalam katagori mendukung (47,2%). persepsi guru tentang komponen metode pada kurikulum 2013 berada dalam katagori mendukung (58,3%). persepsi guru tentang komponen evaluasi pada kurikulum 2013 berada dalam katagori tidak mendukung (50%).Kata kunci : Kurikulum 2013, Persepsi guru, tujuan kurikulum 2013